Expert System Diagnosa kerusakan jaringan LAN Dengan Menggunakan Forward Chaining di Raza Net Kalideres - Hermayanto; Ferry Ferdiansyah; Adam Setiya Mustaqim; Hendrik Gunawan (BISIK : Jurnal Ilmu Komputer, Hukum, Kesehatan dan Sosial Humaniora, 2022)
Artificial intelligence (Artificial Intelligence) is a field of computer science that is intended to solve a problem that is generally related to human intelligence, such as the manufacture of software and hardware, an expert system is a computer program that imitates thinking processes and knowledge in solving a problem. In certain cases, expert systems are always designed and implemented and certain programming languages help to solve a problem. Local Area Network (LAN) is a private network located at home, on campus, or in a company in one building. The application of an export system is used to diagnosing disturbances that occur on the LAN network, using the forward chaining method is expected to make it easier to find out the disturbances that occur on the LAN network